EFL STUDENTS’ PERCEPTIONS OF USING EDMODO APPLICATION IN WRITING CLASS DURING COVID-19 OUTBREAK - Renovhya Wisudany Agitha Sutrisno; Sabarun Sabarun; Akhmad Ali Mirza (IKIP Siliwangi, 2022)
The purpose of this study was to determine the perceptions of students in the 2019 academic year on the usage of Edmodo as online learning platforms in the Essay Writing course that has been implemented. The researcher employed a quantitative technique, engaging 40 students from IAIN Palangka Raya's English Study Program. Purposive sampling was used to collect the samples. The information was gathered using closed-ended questionnaires, which included 15 statements separated into four categories. The first section discusses the advantages of using Edmodo, the second discusses the disadvantages of using Edmodo, the third discusses evaluations of using Edmodo, and the last section discusses problems of using Edmodo. Descriptive statistics were used to describe the findings. The employment of Edmodo in the educational process was found to be positively received by the majority of students. Edmodo has made it easier for them to study from home during the pandemic. Besides, some obstacles were also experienced by the students such as the slow internet network and according to them, online learning activities took up a lot of their time. Keywords: Students’ Perception, Edmodo, EFL, Writing, COVID-19 Outbreak